a x ^ 2 + b x + c = 0
The solution to the quadratic equation is given by 2 numbers x1 and x2.
We can change the quadratic equation to the form of:
a x ^ 2 + b x + c = a ( x - x1 ) * ( x - x2 )
a = 1 so
x ^ 2 - 6 x + 12 = 1 * ( x - x1 ) ( x - x2 ) = ( x - x1 ) ( x - x2 )
For : x ^ 2 - 6 x + 12 = 0
the solutions are:
x1 = 3 - i * sqroot ( 3 )
x2 = 3 + i * sqroot ( 3 )
x ^ 2 - 6 x + 12 = ( x - x1 ) * ( x - x2 ) =
[ x - ( 3 - i * sqroot ( 3 ) ] * [ x - ( 3 + i * sqroot ( 3 ) ] =
[ x - 3 + i * sqroot ( 3 ) ] * [ x - 3 - i * sqroot ( 3 ) ]
what are the factors of x^2-6x+12?
1 answer